Circular dichroism of magnetically induced transitions for D2 lines of alkali atoms. (25th April 2018) - Tonoyan, A.; Sargsyan, A.; Klinger, E.; Hakhumyan, G.; Leroy, C.; Auzinsh, M.; Papoyan, A.; Sarkisyan, D.
Abstract: In this letter we study magnetic circular dichroism in alkali atoms exhibiting asymmetric behaviour of magnetically induced transitions. The magnetic field induces transitions between hyperfine levels of alkali atoms and in the range of magnetic field, the intensities of these transitions experience significant enhancement. We have inferred a general rule applicable for the D 2 lines of all alkali atoms, that is the transition intensity enhancement is around four times larger for the case of than for excitation for, whereas it is several hundreds of thousand times larger in the case of than that for polarization for . This asymmetric behaviour results in circular dichroism. For experimental verification we employed half-wavelength-thick atomic vapor nanocells using a derivative of the selective reflection technique, which provides a sub-Doppler spectroscopic linewidth ( ). The presented theoretical curves well describe the experimental results. This effect can find applications particularly in parity violation experiments.